Comparing Aspects Of The Process Quality In Six European Early Childhood Educational Settings - Zachopoulou, E. (2016)
The European project ‘Early Change’ (http://earlychange.teithe.gr) attempts to evaluate the quality of early childhood education (ECE) environments of six European countries, Greece, Portugal, Finland, Denmark, Cyprus and Romania. The purpose of this paper is to compare the level of two dimensions of the process quality of these environments a) Space & Furnishings, and b) Personal Care Routines. Theorists, practitioners and researchers agree that in order to provide qualitative education to young children, one of the basic needs of all children must be met; that need is the protection of their health and their safety. A high quality early childhood education program must contain a safe and stimulating environment for the child (Lindsey, 1998). Such an environment includes indoor space, outdoor space, furniture, and room arrangement, and it is considered an integral part of a high quality early childhood program. 117 early educators from the six participating countries attended the training seminars about the evaluation of ECE quality using the Early Childhood Environmental Rating Scale-R (ECERS-R). The trained educators evaluated the 8 indicators of the subscale ‘space & furnishings’ and the six indicators of the subscale ‘personal care routines’ in approximately 600 early childhood classrooms from six European countries. The results of this study highlight the similarities and differences concerning the specific dimensions of the process quality of ECE environments in six European countries, and reflect the diversity of ECE environment across these countries. The findings of this study may provide a valuable insight to researchers and educational policy makers for an enhanced understanding of the cultural diversities and the strengthening of the common values and targets of the European Union.